Tratamiento de la endometriosis I y II: Revisión de la literatura A review of the literature concerning treating endometriosis I and II - Ivonne Jeannette Díaz-Yamal; Alef Tsade Sanabria-Gaitán (Federación Colombiana de Obstetricia y Ginecología, 2008)
Objetivo: el objetivo de este manuscrito es hacer una revisión de la literatura disponible que aborde el tratamiento de la endometriosis I y II para el manejo del dolor, de la infertilidad y como coadyuvante en las técnicas de reproducción asistida. Metodología: se realizó una revisión de la literatura disponible en las bases de datos PubMed/Medline con énfasis en guías de manejo desde 1992 hasta 2007. Resultados: en el tratamiento del dolor en endometriosis I y II, tanto el manejo médico como quirúrgico es efectivo. No hay diferencia entre los diversos tratamientos médicos en la disminución del dolor; su elección estará determinada por la edad, el deseo de fertilidad de la paciente y los efectos secundarios de los mismos. Para el tratamiento de la infertilidad asociada a endometriosis, el tratamiento médico no es efectivo, pero el manejo quirúrgico parece benéfico para los estadios I y II, eliminando los focos de la enfermedad. Conclusión: se requieren más estudios aleatorios controlados, comparando su uso con placebo o sin tratamiento. La cirugía también ha demostrado mejoría, pero no existen estudios que comparen el manejo médico con el quirúrgico. Objective: this manuscript was aimed at reviewing the available literature concerning treatment for endometriosis I and II in managing pain, infertility and as coadjuvant in assisted-reproduction techniques. Methodology: the literature available in Pub-Med/Medline databases was reviewed, emphasising management-guidelines published between 1992 and 2007. Results: endometriosis is usually defined as being the presence of endometrial functional tissue from the uterine cavity found growing on organs in other parts of the body. Its form of presentation changes froms light forms lacking adherente (I-II) to severe forms accompanied by retraction and fixation of peritoneal, ovary and tubaric surfaces (III - IV). Endometriosis predominantly appears in females during their reproductive age, average age for onset of symptoms being 20,1 6,8; occurring in all ethnic groups. Its prevalence is estimated as being 10%; nevertheless, it is found in 40% to 60% of females consulting for pelvic pain and in 20% to 30% of those who consult for infertility. Conclusions: no difference was found between different medical treatments in terms of reducing pain, choice of treatment being determined by a patient's age, the desire for becoming fertile and the indirect effect of such. Nevertheless, more random controlled studies are required for comparing their use to placebo or without treatment. Surgery has also been demonstrated to induce improvement, but no studies were found comparing medical to surgical handling. Medical treatment of endometriosis-associated infertility was not seen to be effective; however, surgical treatment seemed to be beneficial for states I and II in eliminating disease foci.